Le mythe et le réenchantement de l’écriture, Albert Camus et Romain Gary en quête d’une parole originelle - Chikhi, Mohamed Nassim (Journal of Human Sciences, 2016)
Albert Camus and Romain have in common to have placed the myth at the heart of creative writing business. They tried to return his existential dimension to the literature by integrating the power of mythic expression in the novel. The myth thus offers the opportunity of an encounter between two works that may at first seem very different view. This article precisely to connect thought and imagination of these writers to show how big the mythical expression taken as literature, to finally see what was their conception of myth, how they themed and incorporated in its various incarnations , in their respective works.